PENGARUH MODULUS KEHALUSAN AGREGAT HALUS TERHADAP BETON MUTU TINGGI SCC - Andryadi, Andryadi; Firdaus, Firdaus (Fakultas Teknik Universitas Muhammadiyah Sumatera Barat, 2026)
One type of concrete that is now increasingly popular is Self Compacting Concrete (SCC). SCC is concrete that has the ability to flow on its own, filling the mold completely without the need for mechanical vibration. Fine aggregates in concrete play an important role in achieving the quality of SCC concrete. The fineness modulus of fine aggregates, which refers to the size and distribution of aggregate particles, has the potential to affect the performance of the concrete mix. Aggregates with a low fineness modulus have coarser and larger particles. The purpose of this study was to analyze the effect of variations in the fineness modulus of fine aggregates on the quality of Self-Compacting Concrete (SCC). The results of the study show that the fineness modulus of fine aggregate has a significant effect on the compressive strength, tensile strength, and elastic modulus of high-quality SCC concrete. The optimum value was obtained at FM 2.21, with the following average results: Compressive strength: 67.4 MPa, Split tensile strength: 5.19 MPa, Modulus of elasticity: 44.13 GPa. The effect of a smaller FM (finer fine aggregate) resulted in a denser concrete mixture and higher compressive strength. Keywords: SCC; Modulus smoothness; Modulus of elasticity; Tensile strength; Compressive strength